Training to Improve the Knowledge and Skills of Junior High School Students in the Field of Electrical Installation - Supriyono, Heru; Adi, Nurhadi Dharmaputra Permata; Yudha, Anas Awali (Journal of Community Services and Engagement: Voice of Community (VOC), 2023)
The partner of this social service activity is the Muhammadiyah 11 Junior High School Special Program as part of the residents in the preaching area of the Muhammadiyah Branch Management (PCM) of Nogosari, Boyolali Regency. Regarding electrical installation, the problem faced by partners is that many students are still unfamiliar with electrical installation especially on technical specifications. The objective of this social service is to increase the knowledge and skills of students in electrical installation. The method of implementing the service is in the form of socialization and training in 3 meetings with material including the basics of electrical installation, KWH meter readings, knowledge of cables and connections, electrical installation equipment, and the use of equipment in electrical installations. The effectiveness of the activities was evaluated by conducting pre-tests, post- tests and direct observations on training participants. The evaluation results showed that the training activities were able to increase knowledge, namely students are able to answer between 1-3 questions correctly when the pre- test increases to 5-13 questions during the post-test, the skills and motivation of the participants in the field of electrical installation. However, further training activities are still needed with more in-depth materials and a longer duration.